The role of human disturbance in the dynamics and distribution of sand forest in and around Tembe Elephant Park, KwaZulu-Natal. - Brereton-Stiles, Ronwyn (Department of Environmental and Geographical Science, 2023)
This study investigated the nature and effects of a number of human disturbances' on the spatial distribution and dynamics of sand forest in and around Tembe Elephant Park (TEP). Maputaland, South Africa The first disturbance investigated was that of fire and its role in determining the spatial patterning of sand forest at the landscape level. Secondly human disturbance was investigated i11 the fom1 of utilisation of forest products and the effects of this on the d}11amics of sand forest as a ·whole as well as on individual species. Sand forest in this area was restricted to deep \ilite sands and occurred as patchy strips mlh a north-south onen.latio11 within a mosaic of grassland and wooded grassland. An abrupt forest grassland boundary was evident in these patches. Two alternatives were investigated as causal factors of the observed patterning: firstly, that sand forest boundaries could be set by underlying soil conditions and thus mosaic components were static; secondly that patches could be remnants of larger tracts of forest, such were fragmented or maintained by past disturbances such as fires. In the absence of these disturbances, patcl1es should be able to expand. II was found that mosaic components did not differ significantly between altin1de (used as a surrogate for s1il moisture) which could imply that distribution patlems are not solely governed by Sil determinants. Prevailing and direction and intensity over tl1e dry (fire) season were fol.llld lo be strongly southerly and n1,rtherly and this is considered 10 be the direction for fratllentation and maintooance of north-south orientated strips. Evidence of bush clumping in ti1e grassland occurred around Dum .whletteri nuclei. 'Ibis process appears lo be slow as. although evidence of thickening in lire-protected areas occurred in aerial photographs over time, it is gradual. The removal of lire in the grassland should lead to the development of sand forest clumps. llie dynamics of sand forest in terms of composition and size-class distributio11s was compared between a marginally disturbed site used by people south of the reserve and an unharvested site within the reserve from which elephants had been excluded. Overall dynamics were found be similar between the sites although certain species showed significant higher densities of seedlings in disturbed sites than in protected sites. Canopy dominants were found to have low levels of seedling recruitment and an analysis of the 'grain· of sand forest showed it to ha'e a course grain relative to other forest types in KwaZulu-Natal. TI1ese finding imply tliat relatively large gaps may be needed within sand forest in order to allow for regeneration of canopy species. four types of human use of sand forest products were investigated in the context of their sustainability medicinal, cmfl and fuehvood sales and hut building. A number of plant products were harvested for the medicinal trade. Of the species investigated, the bark of Cassipourea mossambicensis appeared 10 be harvested unsustainably and this species has been seriously impacted outside the reserve. Crafters targeted Clei.rtanlhus schlecteri for the manufacture of bowls for sale along the roadside. A model of a population of these trees adjacem to the main crafi stalls revealed that reproductively viable adult troos would be depleted within 25 years. This indicated lhat era.ft manufacture was unsustainable. Newtonia hifdebrandtii was the most commonly sold fuelwood along lhe roadside. Sellers mainly used deadwood and turnover rates of bundles sold was .1remely slow. TI1us al the time of the study (1997) fuehvood sale appeared to be sustainable. The main framework of huts built was composed of thin understorey and subcanopy sand forest woody species. Strong evidence of resprouting occurred in these species and species composition of huts was similar to an earlier study underrnken in J 982. This suggested lhat impact 011 forest dynamics was not substantial for this type of use. In conclusion, management and utilisation of sand forest needs to be within the dynamics and regeneration capacity of this forest and its constituent species. t'or example l predict that an absence of fire will lead to tltickcning of woody 'egetation and a decline of grasslands. Canopy species may require large gaps for regeneration to take place. vse of plant products for commercial purposes (e.g. C. mossambicensis for bark and C. schfecferi for crafts) is unsustainable given the slow growth rates of the forest. Allhough sale of tirewood appeared to be sustain.able at the time of the study, with increasing demand rrom tourists. live trees may increasingly be used and this industry could soon be problematic. U1ilisation of trees for domestic purposes appeared lo be sustainable as sand forest species were resilient resprouters. However, commercial use of this forest type was felt to be unsustainable. Species found to be most at risk were C mossambicensis, C. schlecteri, and N. hildebrandtii.